Step-by-step explanation:
'u squared minus t squared' is u²-t².
If we use the difference of two squares theorem we can write it as:
![u^2-t^2=(u+t)(u-t)](https://img.qammunity.org/2023/formulas/mathematics/college/4mnvxdsftol80ngc1fk2vm0cp4txf299mo.png)
We have that
• u + t = 8
,
• u - t = 3
So u squared minus t squared is:
![u^2-t^2=(u+t)(u-t)=(8)(3)=24](https://img.qammunity.org/2023/formulas/mathematics/college/94ktk2wqteqleh7edzvnghnl8x85108o0k.png)
Answer:
The value of u squared minus t squared is 24